La territorialisation du quick commerce à travers le cas des dark stores à Paris - Maxime Schirrer; Erika Nahay; Lise Phan (Netcom)
The transformation of consumption patterns linked to the development of digital platforms has had a profound impact on the forms of commerciality in the city. This article is based on a study of dark stores, to analyze repercussions of quick commerce on public space with the emergence of new uses. While regulations have struggled to regulate these new activities, the materiality of digital platforms is immediately visible and raises questions about the city's capacity to integrate new economic activities.